Antropologiczne podstawy koncepcji zrównoważonego rozwoju z perspektywy ekonomicznej: od homo oeconomicus do homo sustinens - Fiedor, Bogusław (Anthropological foundations of sustainable development concept from the economic perspective: from homo oeconomicus to homo sustinens, 2006)
The paper starts with presenting the way in which anthropological foundations of Sustainable Development concept are perceived and analyzed in the contemporary ethics and philosophy, among other things, making up the so called eco-philosophy or even the philosophy of Sustainable Development. Following those general considerations, the author highlights the very nature of anthropological dimension of Sustainable Development from the economic standpoint, paying special attention to microeconomic foundations of the intergenerational equity principle. He briefly discusses differences between mainstream economics (neoclassical environmental economics) and ecological economics with respect to this issue. Based on this, the author formulates the question which he considers fundamental from the point of view of behavioural or microeconomic foundations of Sustainable Development concept: can we identify on the microeconomic level (households, enterprises) values, motives and goals whose implementation or internalization may lead in the macroeconomic and even global scale to outcomes which are consistent with objectives and principles of Sustainable Development. While answering this question the author firstly analyzes linkages between the general neoclassical model of economic behaviour and the intergenerational equity, also pointing out some shortcomings of that model, and especially with regard to the utility maximization hypothesis in the context of the so called market failures. In the final part of the paper, the author discusses the concept of Homo sustinens, based on the hypothesis of sustainability of human race and its natural environment. He considers this hypothesis as an alternative to the neoclassical utility maximization hypothesis, trying to reveal various foundations of Homo sustinens concept, including those highlighted by some non-economic sciences: evolutionary biology, neurobiology and social psychology.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1131, s. 104-119